ENTHALPIES OF MIXING OF THE Ce-Cu-Sb MELTS (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
Enthalpies of mixing of liquid alloys of the ternary Ce-Cu-Sb system, solid alloys of which are the promising thermoelectric materials that demonstrate a series of important electro-physical properties, were simulated through the whole concentration triangle using the thermodynamic data for the binary boundary systems obtained in our previous investigations by means of the Toop "geometric" equation, which was successfully applied to analogous systems previously. The calculated value of minimum integral enthalpy of mixing for ternary melts is equal to –121.4 kJ·mol–1, which is less than the same value in the binary Sb-Ce liquid alloys. A monotone increase of exothermic enthalpies of mixing was established from the copper corner to the Ce-Sb side of the triangle, which has the highest energy of the component interaction among the three binary boundaries of the ternary system. This fact allows us to conclude that Sb and Ce interaction provides the main contribution to the energy of ternary alloy formation, the addition of copper atoms only leads to a significant reduction of component interaction of alloys of the Ce-Cu-Sb system. It is also shown that the region of maximum interaction of the components in the liquid state in this system fully corresponds to a concentration range of existence of ternary compounds in the solid state, which indicates the same order of components interaction in the liquid and solid state in studied system. The calculation of the thermodynamic properties of the liquid ternary alloys of the studied Cu-Ce-Sb system is an important stage in establishing the general aspects of phase equilibria in this system, as well as in determination of a relationship between the distinctive features of component interaction in solid and liquid phases.
Keywords: cerium, copper, antimony, enthalpy of mixing.